Growth Response and Yield of Three Shallot Varieties on The Various Mixed of UREA + ZA in Ultisol Soil - Lily Marlina; Joko Purnomo; Hilda Susanti (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2021)
This study aimed to: (1) identify the interaction effect between varieties and mixed doses of urea + ZA on the growth and yield of shallots in Ultisol soil; (2) to identify the effect of each shallot varieties and the dosage mixture of urea + ZA which produce the highest yield in Ultisol soils. The research was conducted from April to June 2019 in Tungkaran Village, Martapura, with a split plot design. The main plot was shallot varieties (V) with three levels, namely Biru Lancor (v1), Bima Brebes (v2), and Super Philip (v3). Subplots were a mixture of urea + ZA (P) with four levels, namely 0 kg urea + 600 kg ZA (p1), 100 kg urea + ZA 400 kg (p2), 200 kg urea + 200 kg ZA (p3), and 300 urea kg + ZA 0 kg (p4). Each experiment was repeated three times. Therefore, there were 36 experimental units. Observation parameters included plant height, number of leaves per clump, number of bulbs per clump, fresh bulbs' weight per clump, and yield of stored dry bulbs. The results showed that the Bima Brebes variety (v2) had a significant effect on plant height, number of leaves, number of bulbs per clump, the weight of fresh bulbs per clump, and yield of stored dry bulbs. The mixture of 200 kg urea + 200 g ZA (p3) significantly affected plant height, number of leaves, number of tubers per clump, the weight of fresh tubers per clump, and yield of stored dry tubers.